Global Investment Promotion Benchmarking Report : Eyes on COMESA - Multilateral Investment Guarantee Agency; International Finance Corporation; World Bank (World Bank, Washington, DC, 2017)
Many countries are convinced that Foreign Direct Investment (FDI) should be an important component of their growth strategy. To encourage FDI, they have improved their business climates, developed various guarantees for investors, and offered incentives. In the real world, Investment Promotion Intermediaries (IPIs) face tight budget and human resource constraints. Allocating scarce resources among the various possible activities is a major component of developing an effective promotion strategy. Research, including that covered in this report, suggests that many IPIs are failing to devote enough attention to the most basic-and least costly-promotion function, one that, if it fails, undermines all other promotion activities. Provision of services to potential investors-and particularly the provision of information-is basic to all promotion. Image-building efforts can be hugely expensive. Similarly, targeted missions and personal selling are costly in terms of both time and effort. FDI offers the prospects of growth and jobs to host countries, but attracting it requires a good deal of effort. Effective investment promotion is not only less costly than adding on more incentives for investors; reform and incentives are unlikely to accomplish their goals without promotion. Promotion efforts will, however, fail to attract desired investment if IPIs are not skilled at the most basic function: collecting and providing to potential investors relevant and timely information. Ensuring that this function works well should be the top priority in the promotion strategy and in the development of management systems.